USING TELEGRAM CHATBOT AS A MEANS OF AUTOMATING THE EDUCATIONAL PROCESS (Innovative professional education, 2025)
This article presents the experience of using the Telegram messenger as a means of supporting the educational process in teaching the educational component «Methods of Teaching the Educational Field ‘Informatics’« at a professional pre-higher education institution under conditions of forced quarantine restrictions and the full-scale Russian invasion of Ukraine. The relevance of using messengers in the educational process is analyzed due to their popularity among students of the corresponding category. The advantages and disadvantages of using messengers for performing certain pedagogical tasks are highlighted. The functionality and possibilities of using the Telegram messenger to support the educational process, in particular through the creation of a chatbot for the academic discipline, are outlined.
Keywords: professional pre-higher education, messengers, chatbot, educational component, educational contentcolleges